The development of interactive multimedia learning media on cell materials in Class XI IPA SMA Negeri 2 Kabanjahe - Nadia Br Ginting; Hudson Sidabutar (ARKA INSTITUTE, 2022)
This study aims to develop and produce interactive multimedia-based biology learning media using a valid, practical and effective powerpoint media that can be applied as a biology learning medium on cell material. The type of research used is development research with a 4-D development model. This model includes four stages, namely defining, designing, developing and disseminating. The results showed: (1) The validity of the media based on the assessment of media experts and material experts by getting an average percentage of 85.5% with the criteria of